IDENTIFIKASI SUB SEKTOR PERTANIAN DI EKS KARESIDENAN KEDU (PENDEKATAN MINIMUM REQUIREMENTS TECHNIQUE) - Dinan Azifah; Agustono Agustono; Nuning Setyowati (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
The  objectives  of  this  study  are  (1)  identify  the  Agricultural  sub  sector  of base and non-base in Kedu Residency (2) develop the Agriculture sub sector of base in Kedu Residency. The results, the food crops subsector basis in Kebumen, Magelang,Wonosobo, Temanggung. Sub Sector Crops base in Kebumen, Purworejo, Magelang, Temanggung.  Livestock  subsector  base  in  Kebumen,  Magelang,  Wonosobo, Temanggung. Forestry subsector base in Kebumen, Purworejo, Magelang, Wonosobo.Fisheries subsector base in Kebumen, Purworejo, Magelang, Wonosobo. Food crops subsector  non  bases  in  Purworejo,  plantation  subsector  in  Wonosobo,  livestock subsector in Purworejo, forestry and fisheries subsector in Temanggung. Development of  food  crops  subsector  in  Kebumen  to  maximize  production,  agribusiness development  in  Magelang,  in  Wonosobo  processing  performed  and  marketing,  in Temanggung  the  marketing  of  agricultural  products.  Development  of  the  plantation subsector  in  Kebumen  the  development  of  HR  trained,  in  Purworejo  improving  the marketing,  in  Magelang  the  development  of  conservation  areas,  in  Temanggung increasing  marketing  and  post-harvest  processing.  Development  of  the  livestock subsector  in  Kebumen  providing  capital  strengthening,  in  Magelang  increased productivity through improved genetic quality,  in Wonosobo revolsin Funds budgeted for  the  farm,  in  Temanggung  increase  in  value-added  farm.  Development  of  the forestry subsector in Kebumen, Purworejo, and Wonosobo did by developing a variety of non-timber business, in Magelang conservation of forest resources. Development of the fisheries subsector in Kebumen improving the marketing, in Purworejo increase fisheries production, in Magelang managing and marketing of fisheries production, in Wonosobo provision of adequate infrastructure.